Perceived social support among adolescents in public schools in areas of social vulnerability - Pascoal, Carlos Eduarde Bezerra; Carraro, Bruna; Meira, Gabriela de Figueiredo; Castilho, Ana Virginia Santana Sampaio; Mendes, Rharessa Gabrielly Ferreira; Trench, Leonardo; Castro, Marcelo Salmazo; Euzébio, Maria Júlia; Foggiato, Lucca Augusto Ribeiro; Peres, Silvia Helena de Carvalho Sales (Seven Editora, 2024)
Adolescence is a time of intense change, where emotional support from friends, family, and teachers plays a crucial role. Mental health problems are common at this stage, highlighting the importance of social support in promoting well-being. The objective of this study was to describe the social support perceived by high school adolescents in public schools located in an area of social vulnerability in the city of Bauru, São Paulo. This was a cross-sectional study.  Data collection was carried out through forms through Google Forms. Support was measured using the Social Support Appraisals (SSA) instrument and the gender of the participants was self-reported. The results show that family support is the source most valued by adolescents, followed by friends and, to a lesser extent, teachers. Friendships are highlighted as an important source of emotional support, evidencing reciprocity and trust among young people. However, teacher support was the least noticed, indicating a disconnect that can impact school wellbeing. Therefore, it is necessary to strengthen social support networks, especially in the school environment of adolescents in contexts of social vulnerability. DOI:https://doi.org/10.56238/sevened2024.026-056